2001
DOI: 10.1070/rc2001v070n01abeh000574
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis in the chemistry of free radicals

Abstract: Published data now available on the use of correlation Published data now available on the use of correlation analysis in free-radical chemistry are discussed systematically. The analysis in free-radical chemistry are discussed systematically. The scales of `radical' scales of `radical' s s-constants of substituents proposed previously -constants of substituents proposed previously are analysed. It is shown that none of them is applicable as a are analysed. It is shown that none of them is applicable as a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 219 publications
0
14
0
Order By: Relevance
“…However, these values did not satisfactorily correlate with the reaction rates for acetonyl addition. We therefore focused on several other radical‐specific substituent parameters employed in linear free‐energy relationships . For example, kinetic measurements of model radical reactions have been used by Creary and co‐workers as well as Jiang and Ji to define the parameters σ .…”
Section: Resultsmentioning
confidence: 99%
“…However, these values did not satisfactorily correlate with the reaction rates for acetonyl addition. We therefore focused on several other radical‐specific substituent parameters employed in linear free‐energy relationships . For example, kinetic measurements of model radical reactions have been used by Creary and co‐workers as well as Jiang and Ji to define the parameters σ .…”
Section: Resultsmentioning
confidence: 99%
“…The main problems arose with the radical stabilization molecular descriptor (σ RS ). In fact, the Hammett constants σ U and σ R (delocalization effect) are not the most suitable to take into account the radical stabilization . A lot of work had already been done in that field but mainly on the benzylic-type compounds .…”
Section: Resultsmentioning
confidence: 99%
“…However, it gives only a rough estimation of the value of k d and is strongly dependent on the accuracy of the value of BDE(C−H). Indeed, other effects such as steric and polar effects in the ground state can bias the values of BDE (C−H). Furthermore, we have recently shown that the correlation log k d vs BDE(C−H) for SG1 derivatives is more complicated than expected from the well-known TEMPO derivative case . To overcome these difficulties, we present hereafter an analysis following a multiparameter approach where log k d is parametrized with the molecular descriptors corresponding to the polar inductive/field (σ U ), steric , (υ), and the stabilization (σ RS ) effects of the leaving alkyl radicals in the TEMPO− and SG1−alkoxyamine series.…”
Section: Introductionmentioning
confidence: 99%
“…According to the methylenology principle, Michael additions of alcohols at intrinsically nucleophilic CC double bonds could be mediated by linking the electron-rich π-system with an electron-accepting group through a radical center. As C-centered radicals are efficiently stabilized by captodative effects, vinyl-substituted α-amino nitriles would be ideal substrates for testing this approach.…”
mentioning
confidence: 99%
“…Therefore, Michael-type addition of alcohols to the terminal C-4 may generate intermediates E , in which the negative charge is delocalized and efficiently stabilized by the electron-withdrawing cyano group. Fast proton transfer converts E to radicals F , which benefit from captodative stabilization . Deuteration at C2 in product 3a ′ was not observed (see above).…”
mentioning
confidence: 99%